Eosinophilic Fasciitis with Isolated Hand Involvement: A Diagnostic Challenge - Wang, Ping; Guo, Mingwen (Archives of Rheumatology, 2025)
Dear Editor, We present this case to highlight an atypical clinical manifestation of eosinophilic fasciitis (EF), which predominantly involved the hands without systemic features—a scenario rarely reported in the literature. This case underscores the diagnostic challenges posed by localized EF and emphasizes the importance of early recognition to prevent irreversible fibrosis.